Web-based Population Information System (Case Study of Ketapang Village Hall Office) - Irene Elvariani Dewanti; Rohman Dijaya; Nuril Lutvi Azizah; Ade Eviyanti (CV. Media Digital Publikasi Indonesia, 2025)
The development of information technology has brought significant changes in various aspects of life, including in the management of population data at the village level. Conventional population information systems that still use manual methods often have various problems such as data inconsistency, difficulty in finding information, and slow administrative service processes. Therefore, this research aims to develop a web-based village population information system that can overcome these problems. This web-based population information system is designed using a waterfall system development approach. Data collection methods were conducted through interviews, observations, and documentation studies. The system was built using PHP programming language and MySQL database. The results showed that this web-based population information system is able to present population data accurately, quickly, and easily accessible by the community and village officials. With this web-based population information system, it is expected to improve the efficiency and effectiveness of population data management at the village level, as well as provide convenience for the community in accessing information and obtaining population administration services.